Clinical manifestations and risk factors for complications of philadelphia chromosome-negative myeloproliferative neoplasms - Boonlerd Duangnapasatit (2018)
Background: Myeloproliferative neoplasms (MPNs) are clonal hematopoietic stem cell disorders characterized by proliferation of one or more myeloid lineages. Polycythemia vera (PV), essential thrombocythemia (ET) and primary myelofibrosis (PMF) are classical Philadelphia chromosome (Ph)-negative MPN that have a Janus Kinase 2 (JAK2) mutation, especially JAK2V617F in the majority of patients. The major complications of Ph-negative MPNs are thrombosis, hemorrhage, and leukemic transformation. Objective: To study clinical manifestations including symptoms, signs, laboratory findings, and JAK2V617F mutations of Ph-negative MPN (PV, ET and PMF) as well as their complications. Materials and Methods: All Ph-negative MPN (PV, ET and PMF) patients who attended the Hematology Clinic at Maharaj Nakorn Chiang Mai Hospital from January, 1 2003 through December, 31 2013 were retrospectively reviewed for demographic data, clinical characteristics, complete blood count, JAK2V617F mutation analysis, treatment, and complications. Results: One hundred and fifty seven patients were included in the study. They were classified as PV, ET and PMF for 68, 83 and 6 with median ages of 60, 61, and 68 years, respectively. JAK2V617F mutations were detected in 88%, 69%, and 100% of PV, ET and PMF patients. PV had the highest incidence of thrombosis (PV 29%, ET 14%, and PMF 0%) that occurred in both arterial and venous sites whereas PMF had the highest incidence of bleeding (PMF 17%, ET 11%, and PV 7%). During follow up, there was one ET patient that transformed to acute leukemia and five cases that developed thrombosis (three ET and two PV patients). No secondary myelofibrosis and death cases were encountered. Conclusions: Ph-negative MPNs have various clinical manifestations. JAK2V617F mutations are present in the majority of PV, ET, and PMF patients. This study confirmed that thrombosis and bleeding are the most significant complications in patients with Ph-negative MPN.